«Ազգ»-ի գիտական ուսումնասիրության բանաձևերը «Ազգագրական հանդես»-ում (առաջին համարի «հրատարակչից» բաժնի քննություն) - Գաբրիելյան, Մխիթար (Հայաստանի պատմության թանգարան)
“Ethnographic Journal” founded in 1896 plays an important role not only in terms of recording, description and analysis of ethnographic materials, but also for the establishment and further development of ethnography in Armenia. Publisher of the journal Yervand Lalayan had formulated the state of the study of Armenian ethnography, identify the problems of national culture in a two-page introductory article entitled “From the Publisher” of the first issue of the journal. Основанный в 1896 г. журнал «Азгагракан андес» («Этнографический журнал») сыграл важнейшую роль не только в деле сбора этнографического материала, ее описания и анализа, но и в процессах становления этнографии и ее дальнейшего развития. В первом номере журнала, всего в двухстраничном материале, заглавленном «От издателя», Ерванд Лалаян смог проанализировать состояние армянской этнографии, выявить стоящие перед наукой основные проблемы.
Keywords: Ազգագրություն